Antimicrobial activity of consecutive extracts of etlingera brevilabrum - Behnam Mahdavi; Yaacob, W.A; Laily B. Din; Nazlina, I (Universiti Kebangsaan Malaysia, 2012)
Disc diffusion (DD), minimum inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) assays were used to evaluate the antimicrobial activity of 21 consecutive extracts of different aerial parts of Etlingera brevilabrum against 18 microorganisms that included six Gram-positive [(+)], ten Gram-negative [(-)] bacteria and two fungi. Among the plant parts, the stolon extracts showed numerous activity than the other parts in which they inhibited Gram-positive of Staphylococcus aureus (ethyl acetate extract: diameter of inhibition zone 12.2±0.3 mm, MIC 3.12 mg/mL, MBC 6.25 mg/mL), methicillin resistant S. aureus (MRSA) (ethyl acetate extract: 12.1±0.2 mm, 12.5 mg/mL, 25 mg/mL), S. epidermidis (ethanol extract: 11.4±0.5 mm, 3.12 mg/mL, 3.12 mg/mL), Bacillus thuringiensis (acetone extract: 13.3±0.5 mm, 12.5 mg/mL, 25 mg/mL) and one Gram-negative of Vibrio paraehaemolyticus (water extract: 14.3±0.4 mm, 1.56 mg/mL, 6.25 mg/mL). The highest activity in MIC was shown by the methanol-water (1:1) and water extracts on Gram-negative Aeromonas hydrophila (1.56 mg/mL: leaf water extract) and V. paraehaemolyticus (1.56 mg/mL: methanol-water and water extracts of stolons and leaves and stem water extract).